2014
DOI: 10.1097/lgt.0b013e31829a5558
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Vaginal Metronidazole for Recurrent Bacterial Vaginosis—A Pilot Study

Abstract: Cure rates for BV were high in this refractory cohort and seemed dose dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
(9 reference statements)
0
10
0
2
Order By: Relevance
“…14 Clinicians caring for women with BV may consider home screening, 15 probiotics, 16 suppressive antibiotics, or the provision of antibiotics to use when symptoms recur, to minimize delay arising from need for a clinician visit. 17…”
Section: Discussionmentioning
confidence: 99%
“…14 Clinicians caring for women with BV may consider home screening, 15 probiotics, 16 suppressive antibiotics, or the provision of antibiotics to use when symptoms recur, to minimize delay arising from need for a clinician visit. 17…”
Section: Discussionmentioning
confidence: 99%
“…Традиційна схема лікування дозволяє швидко усунути симптоми дисбіозу, тому що антибактеріальні препарати пригнічують патогенну та умовно-патогенну флору. Однак дисбіотичні прояви при цьому посилюються, оскільки одночасно відбувається пригнічення пулу лактобацил, що зумовлює потенціювання загальних процесів дисбактеріозу (рецидиву) (Aguin et al, 2014).…”
Section: таблицяunclassified
“…12 The high-dose metronidazole regimen suggested improved cure rates in comparison with prior studies in this refractory population and potential for use as a maintenance regimen. In our preceding pilot study in a treatment-resistant population, we found that the short-term clinical cure rate was high with daily intravaginal metronidazole 750 mg for 7 days.…”
mentioning
confidence: 90%
“…12 If symptomatic BV recurred and was confirmed by Amsel criteria (4 of 4), the patient was dropped from the first study and enrolled into the current study. Eighteen women with severe recurrent BV were enrolled.…”
mentioning
confidence: 99%